2005
DOI: 10.1021/jp050599v
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Neutral Polymer (PVP) on the Solvatochromic Properties of SDS Micelles

Abstract: In the present work, we have studied the influence of a water-soluble neutral polymer (poly-N-vinyl pyrrolidin-2-one, PVP) on the Kamlet-Taft polarity parameters of sodium n-dodecyl sulfate (SDS) micelles. We have used pyrene as an independent dipolarity/polarizability (pi parameter) descriptor molecule. It has been found that the addition of polymer (0.1 wt % PVP) increases the pi value of SDS micelles, suggesting that PVP-SDS aggregates have a larger dipolarity/polarizability than that of SDS micelles. Linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Solution interactions between SDS and PVP have been observed in many contexts; , Goddard has reviewed the interactions between many water-soluble uncharged polymers and charged surfactants. Rheological analysis showed that the viscosity of aqueous PVP solution increases to a value expected for typical polyelectrolytes upon binding ionic surfactants .…”
Section: Introductionmentioning
confidence: 99%
“…Solution interactions between SDS and PVP have been observed in many contexts; , Goddard has reviewed the interactions between many water-soluble uncharged polymers and charged surfactants. Rheological analysis showed that the viscosity of aqueous PVP solution increases to a value expected for typical polyelectrolytes upon binding ionic surfactants .…”
Section: Introductionmentioning
confidence: 99%
“…10,12−24 Ion-dipole interaction between the micelles and the polymer is one of the molecular mechanisms that has been suggested for this phenomenon. [18][19][20][21]25 Ternary systems comprising one polymer and two surfactants have been recently studied. 25−30 Most of the studies involved a neutral polymer, an anionic surfactant, and a nonionic surfactant.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 The cmc of SDS in the presence of NH 2 -(a,L-lysine) 5 -COOH at pH 5.0 is slightly decreased to about 7.8 mM most likely because NH 2 -(a,L-lysine) 5 -COOH is a small molecule as compared to reported polymers with a much larger molecular weight. 16,17 In contrast, the cmc of SDS in the presence of NH 2 -(a,L-lysine) 5 -COOH at pH 11.0 markedly dropped to 4.0 mM, a value 2-fold lower than that of SDS alone (Fig. S3, ESI †).…”
mentioning
confidence: 97%